2019
DOI: 10.1017/s0022149x19000890
|View full text |Cite
|
Sign up to set email alerts
|

A socio-economic study of Fasciola infections in cattle and sheep at the Etoudi slaughterhouse, Yaoundé, Cameroon

Abstract: A cross-sectional socio-economic study of fascioliasis in livestock was carried out at the Livestock Development Cooperation (SODEPA) slaughterhouse in Etoudi, Yaoundé during the periods covering the beginning and late dry season in the northern and eastern regions of Cameroon. A total of 768 cattle and 267 sheep were inspected for the presence of Fasciola species. The overall infection rate in cattle and sheep was 18% (n = 767) and 27% (n = 267), respectively. For the animals that were Fasciola positive, a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
4
4
0
Order By: Relevance
“…(0.33%). The prevalence obtained for Fasciola gigantica is similar to that found by Simo et al (2021) at the Bangangté municipal abattoir (33%), but much higher than that found by Ntonifor & Ndaleh (2012) and Takang et al (2019) in Yaoundé and Douala respectively. As the latter two cities belong to different agro-ecological zones from our study area, this result could reflect spatial variation in stave distribution in Cameroon.…”
Section: Discussionsupporting
confidence: 87%
“…(0.33%). The prevalence obtained for Fasciola gigantica is similar to that found by Simo et al (2021) at the Bangangté municipal abattoir (33%), but much higher than that found by Ntonifor & Ndaleh (2012) and Takang et al (2019) in Yaoundé and Douala respectively. As the latter two cities belong to different agro-ecological zones from our study area, this result could reflect spatial variation in stave distribution in Cameroon.…”
Section: Discussionsupporting
confidence: 87%
“…28 Similar studies in Ethiopia and Cameroon showed a lower Fasciola prevalence with estimated losses from liver condemnations of USD 43,000 and USD 76,000 per year, respectively. 29,30 In these settings, Fasciola not only inflicts an economic burden on smallscale producers but also threatens food security among subsistence farmers that raise livestock to feed their families.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the uncontrolled contaminated feeding of animals in their original breeding grounds. The correlation between infection rate and seasons has been observed in several previously published studies conducted in different countries around the world 36 , 39 41 . The season with the highest infection rate varies from study to study, which can be attributed to the differences in climate and geographical topology.…”
Section: Discussionmentioning
confidence: 60%